Process evaluation of an implementation intervention to facilitate the use of the Swedish Physical Activity on Prescription in primary healthcare - Catharina Gustavsson; Maria Nordqvist; Åsa Bergman Bruhn; Kristina Bröms; Lars Jerdén; Lena V. Kallings; Lars Wallin (BMC, 2023)
Abstract Background The Swedish Physical Activity on Prescription (PAP-S) is a method for healthcare to promote physical activity for prevention and treatment of health disorders. Despite scientific support and education campaigns, the use has been low. The aim of this study was to perform a process evaluation of an implementation intervention targeting the use of the PAP-S method in primary healthcare (PHC). Specifically, we wanted to evaluate feasibility of the implementation intervention, and its effect on the implementation process and the outcome (number of PAP-S prescriptions). Methods This was a longitudinal study using the Medical Research Council guidance for process evaluation of a 9-month implementation intervention among healthcare staff at three PHC centres in Sweden. Data was collected by: participatory observations of the implementation process; questionnaires to the staff before, after and 6 months after the implementation intervention; interviews after the implementation intervention; and number of PAP-S prescriptions. Results During the implementation intervention, the workplaces' readiness-to-change and the healthcare staff's confidence in using the PAP-S method were favourably influenced, as was the number of PAP-S prescriptions. After the implementation intervention, the number of PAP-S prescriptions decreased to about the same number as before the implementation intervention, at two out of three PHC centres. Four of the six implementation strategies appeared to impact on the implementation process: external facilitation; leadership engagement by a committed workplace management; local PAP-S coordinator taking a leading role and acting as local champion; educational outreach concerning how to use the PAP-S method. Conclusion The implementation intervention was not sufficient to produce sustained change of the healthcare staff's behaviour, nor did it achieve favourable long-term outcome on the number of PAP-S prescriptions. The healthcare staffs' sparse knowledge of the PAP-S method prior to the implementation intervention hampered the implementation. More hands-on education in how to use the PAP-S method introduced early in the implementation process is imperative for successful implementation of the PAP-S method. The findings also suggest that committed workplace management and local PAP-S coordinators, taking leading roles and acting as local champions, need to be firmly established at the PHC centres before the external facilitator withdraws. Trial registration Registered in the ISRCTN registry with study registration number: ISRCTN15551042 (Registration date: 12/01/2016).